Correlation between histological grading, LVI and PNI of carcinoma oral tongue to lymph node metastasis - C. Viswanatha, Sumana; Hedne, Naveen; Hasan, Suhel (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Squamous cell carcinoma (SCC) of oral tongue has a higher predisposition to lymph node metastasis which reduces survival by 50%. In clinical practice, TNM classification is used for treatment planning which does not provide information on the biological characteristics of the tumor. Methods: This prospective cross sectional observational study included 30 patients with T1 to T3, N0/+ oral tongue SCC from 1st March 2014 to 30th April 2015. Incisional biopsy was taken from the primary tumour, pathological evaluation for differentiation of the tumour and assessment of lymphovascular (LVI) and perineural invasion(PNI) was carried out. Post operative histopathological examination included differentiation, LVI and PNI. The pathological findings were correlated using chi square test. Results: Majority presented with T2 stage. 27% had nodal metastasis. There was higher incidence of lymph node metastasis in moderately differentiated (MD) and poorly differentiated (PD) SCC which was not statistically significant. Significant correlation was seen between LVI and PNI to lymph node metastasis (p≤0.001). Conclusions: There is a higher incidence of lymph node metastasis seen in moderately and poorly differentiated SCC of oral tongue, which can be assessed on the preoperative biopsy, guiding us to be more aggressive in the management of cervical nodes in early tongue cancer. LVI and PNI are good predictors of nodal metastasis, help in assessing aggressiveness and prognosis of the disease, and are soft indicators for considering adjuvant / concurrent RT.